Biopsychosocial Determinants of Quality of Life in the Elderly at Tresna Werdha Social Nursing Home, Yogyakarta - Sobma Swastika; Setyo Sri Rahardjo; RB Soemanto (Masters Program in Public Health, 2017)
Background: Aging process is a multidimensional natural process with implicating problem involving various aspects, i.e. biological, psychological, and social aspects. Efforts are needed to prolong life expectancy and to improve the quality of life of the elderly. This study aimed to analyze biopsychosocial determinants of quality of life in the elderly at Tresna Werdha Social Nursing Home, Yogyakarta.Subjects and Method: This study was analytic observational study with cross-sectional design. It was conducted at Abiyoso and Budi Luhur units, Tresna Werdha Social Nursing Home, Yogyakarta, in April 2017. A sample of 100 elderly were selected for this study by purposive sampling and simple random sampling. The independent variables were health status, level of independence, intellectual function, depression, and social activities. The dependent variable was quality of life. The data were collected by a set of pre-tested questionnaire and analyzed by logistic regression.Results: Biopsychosocial determinants of quality of life in the elderly included health status (OR= 11.66; 95% CI= 2.18 to 62.14; p= 0.004), level of independence (OR= 4.12; 95% CI= 1.08 to 15.60; p= 0.037), intellectual function (OR= 9.75; 95% CI = 1.09 to 87.08; p= 0.036), depression (OR= 3.38; 95% CI= 1.01 to 11.24; p= 0.047), and social activities (OR= 6.02; 95% CI = 1.12 to 32.25; p= 0.047).Conclusion: Health status, level of independence, intellectual function, depression, and social activities, are biopsychosocial determinants of quality of life in the elderlyKeywords: biopsychosocial, determinant, quality of life, elderlyCorrespondence: Sobma Swastika. Masters Program in Public Health, Sebelas Maret University. Jl. Ir. Sutami 36 A, Surakarta, Central Java. Email: sobmaswastika@gmail.com. Mobile: +628113239862.Journal of Epidemiology and Public Health (2017), 2(1): 82-92https://doi.org/10.26911/jepublichealth.2017.02.01.08